Assessment of Labor Condition of Construction Workplace in Banke District, Nepal - Bohara, Asha; Neupane, Uttam; Bhattarai, Subash Kumar; Rokaya, Shovansing (Mid-West University Journal of Engineering & Innovation, 2025)
The article "Assessment of Labor Condition in Construction Workplace in Banke District, Nepal" addresses two main objectives in order to assess the present status of labor conditions in the construction sector. The primary objective is to determine workers awareness regarding Nepalese Labor Act’s provisions, using a yes/no-dichotomous method. The second objective is to determine general working conditions of construction workers on construction sites. The study depends on primary data gathered from questionnaire survey, obtained from construction workers participating in different projects. The study evaluates financial, social, environmental, health and safety, and site management aspects in order to better understand labor conditions in construction workplaces. Surveys targeting construction workers were used to collect data, and Tukey’s HSD test, ANOVA, and the Relative Importance Index (RII) were used for analysis for the second objective. The results show serious issues such as inadequate training programs, a lack of personal protective equipment (PPE), limited health insurance coverage, unpaid wages and delays in payments. The results show that employees are largely unaware of their rights under the Labor Act and draw focus on poor working conditions, such as insufficient safety precautions, a lack of social security, and a lack of effective labor law enforcement. These results highlight the necessity of improved workplace standards, better enforcement of labor laws, and broader labor changes in order to guarantee construction workers’ safety, equality, and financial stability. Improving working conditions by taking these steps is essential to developing a more sustainable and economically viable construction sector.